2013
DOI: 10.1590/0103-6440201302357
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Structural Evaluation of Dentin Caries-Like Lesions Produced by Different Artificial Models

Abstract: This study evaluated structural and molecular issues of dentin caries-like lesions produced by different artificial models (ACL) compared with natural caries lesions (NCL). One hundred twenty-four sound occlusal dentin blocks and 47 carious blocks were obtained and surface hardness was analyzed (SH1). They were assigned to groups according to ACL: GB: Biological; GC: Chemical; GIS: In situ; GNC: natural caries (control). Blocks from groups 1, 2 and 3 were submitted to caries lesion induction. NCL and ACL block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 23 publications
0
33
0
3
Order By: Relevance
“…The in vitro demineralization models commonly use organic acids, chelators, or bacterial biofilms to mimic carious lesions (34‐36). Although in vitro caries models never reproduce all aspects of the clinical situation, sample acquisition is simple and specimens can be treated in a standardized and reproducible way (37).…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro demineralization models commonly use organic acids, chelators, or bacterial biofilms to mimic carious lesions (34‐36). Although in vitro caries models never reproduce all aspects of the clinical situation, sample acquisition is simple and specimens can be treated in a standardized and reproducible way (37).…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to simulate and standardize the conditions found in natural cariesaffected dentin, several methods of producing caries-like lesions in vitro have been developed, such as chemical and biological models (Lenzi et al, 2015;Pacheco et al, 2013). The present study submitted the sound dentin specimens to a chemical demineralizing challenge by applying an acid gel containing lactic acid, a by-product of bacterial metabolism (de Carvalho et al, 2008;Pacheco et al, 2013). It was verified that this method was effective in impairing the TBS values of dentin; furthermore, SEM analysis presented a emineralized dentin exhibiting a heterogeneous and porous surface with some lumens of dentinal bliterated (Figure 2 -B1).…”
Section: Discussionmentioning
confidence: 99%
“…2.4.1. Demineralization procedures Tooth slices (N=108) were immersed in 5 mL of 6% carboxymethylcellulose acid gel (Proderma Pharmacy; Piracicaba, SP, Brazil) containing 1 M lactic acid titrated with a concentrated KOH solution at 37ºC, pH 5.0, for 48 h (de Carvalho et al, 2008;Pacheco et al, 2013). Tooth slices were rinsed twice with deionized water in an ultrasonic bath for 15 min and slightly dried with tissue paper (Sacramento et al, 2012).…”
Section: Dentin Demineralization and Surface Pretreatmentmentioning
confidence: 99%
“…Altered dentin characteristics can affect the resin/dentin bonding interface, since caries-affected dentin leads to greater variability and a highly irregular composition along the interface (9). Although, clinically caries affected dentin shows mineralized precipitates within the tubules (6), Pacheco et al (10) showed that similar mineral content concerning Ca, CO 3 and PO 4 and organic content like CH bonds, may be found also in vitro when S mutans biofilm provided dentin carious lesions compared with the natural ones.…”
Section: Introductionmentioning
confidence: 99%